Targeting mRNA translation in Parkinson's disease. Issue 6 (June 2019) - Correddu, Danilo; Leung, Ivanhoe K.H.
Graphical abstract: Highlights: Parkinson's disease (PD) is one of the most common neurodegenerative disorders. Mutations in the genes that are involved in translation are linked to PD. The link between altered mRNA translation and PD is poorly understood. Future studies aiming at restoring mRNA translation may enable new PD treatments. Abstract : Parkinson's disease (PD) is one of the most common neurodegenerative disorders. The exact cause(s) of PD is not well understood, although genetic mutations are associated with some forms of the disease. Many of these mutations, in particular those that are found in LRRK2, DJ-1, PINK1, and Parkin, are linked to the deregulation of mRNA translation, suggesting that this process is important for the onset of PD. Herein, we highlight recent studies that provide insights into the molecular mechanisms that relate mRNA translation to PD. These studies confirm the central role of translation in PD, emphasising the potential of restoring mRNA translation functionality as a new therapeutic treatment against PD, and providing novel targets for developing new chemical agents to target this disease.